Modeling of the Interminiband Absorption Coefficient in InGaN Quantum Dot Superlattices - Giovanni Giannoccaro; Francesco De Leonardis; Vittorio M. N. Passaro (Photonics, 2016)
In this paper, a model to estimate minibands and theinterminiband absorption coefficient for a wurtzite (WZ) indium gallium nitride (InGaN) self-assembled quantum dot superlattice (QDSL) is developed. It considers a simplified cuboid shape for quantum dots (QDs). The semi-analytical investigation starts from evaluation through the three-dimensional (3D) finite element method (FEM) simulations of crystal mechanical deformation derived from heterostructure lattice mismatch under spontaneous and piezoelectric polarization effects. From these results, mean values in QDs and barrier regions of charge carriers’ electric potentials and effective masses for the conduction band (CB) and three valence sub-bands for each direction are evaluated. For the minibands’ investigation, the single-particle time-independent Schrödinger equation in effective mass approximation is decoupled in three directions and resolved using the one-dimensional (1D) Kronig–Penney model. The built-in electric field is also considered along the polar axis direction, obtaining Wannier–Stark ladders. Then, theinterminiband absorption coefficient in thermal equilibrium for transverse electric (TE) and magnetic (TM) incident light polarization is calculated using Fermi’s golden rule implementation based on a numerical integration into the first Brillouin zone. For more detailed results, an absorption coefficient component related to superlattice free excitons is also introduced. Finally, some simulation results, observations and comments are given.